Analisis Wacana dalam Buku Ajar Bahasa Arab Kelas X Kurikulum Merdeka: Kajian Linguistik Modern - Siti Nurul Hidayah; Dedy Wahyudin; Tia Fatma (Universitas Muhammadiyah Mataram, 2026)
This study aims to identify types of discourse and analyze discourse integration through the aspects of cohesion and coherence in the 10th-grade Arabic textbook for Madrasah Aliyah under the Merdeka Curriculum, published by the Ministry of Religious Affairs of the Republic of Indonesia. The study employs a qualitative descriptive method using a content analysis approach. The data sources consist of all chapters in the textbook, which contain 10–20 discourse texts in the form of dialogues (hiwar) and descriptions as units of analysis. The analysis was conducted using Halliday and Hasan’s theory of cohesion and Beaugrande and Dressler’s theory of coherence. Data collection was carried out through documentation, while data analysis followed the interactive model of Miles and Huberman. The results of the study indicate that the dominant discourse types are dialogues and descriptions structured contextually in accordance with the students’ daily lives. Grammatical cohesion is evident through the use of pronouns, conjunctions, and repetition, while coherence is reflected in the integration of meaning across text segments. These findings suggest that the textbook supports communicative Arabic language learning and aligns with the principles of the Merdeka Curriculum.